Students' Achievement Emotions and Online Learning in Teacher Education - Stephan, Melanie; Markus, Stefan; Gläser-Zikuda, Michaela (Frontiers in Education, 2019)
Online learning has become widely accepted and is considered as an important approach that can overcome the limitations of on-campus learning, especially in higher education. The acceptance of learning technologies generally depends on technology related beliefs and the perceived ease of use. The use of learning technology depends on how students experience it emotionally. Although research on emotions in technology-supported learning environments has increased in recent years, the question how students experience online learning environments emotionally, and how these emotions are intervened with technology acceptance has not yet been answered in more detail. Up to now, only a limited number of studies has focused on emotions and technology acceptance of university students, especially in teacher education. Therefore, the purpose of this study is to analyze students’ technology acceptance and achievement emotions after participating in an online course (in comparison to an on-campus course) in teacher education. Survey data from 182 students (88 of them participated in an on-campus course, 94 students attended an online course) revealed a higher level of positive emotions than of negative emotions, regardless of the learning environment. Students who attended the online course reported a higher level of boredom, anxiety, and anger, but less enjoyment. Furthermore, the results show that online students reported significantly higher levels of achievement task value und technological control. Technological value correlated significantly with enjoyment. In contrast to the theoretical assumptions, no systematic differences were found between the two learning environments for the achievement emotions hope, shame, hopelessness, and anxiety. Regardless of the learning environment, enjoyment was essential for the value that students attach to both, learning content and technology. The online and the on-campus group differed in terms of domain specific achievement outcome. Interestingly, however, these differences cannot be explained by the covariates, the two control and value scales, the technology related beliefs, and age. Main results of the study regarding the control-value theory and implications for online learning environments, as well as limitations of the study are presented and discussed.